An evaluation of treatments and survival rates for pancreatic adenocarcinoma through survival analysis with inverse probability of treatment weighting: a population-based study. Issue 1 (March 2021) - Wang, Suzhen; Wang, Chen; Shi, Fuyan; Tao, Enxue; Zhu, Gaopei; Li, Juan; Feng, Jianing; Wang, Xiaoxuan; Guo, Jing; Zheng, Qingfeng; Zhang, Bo
Abstract: Objective: This study conducted inverse probability of treatment weighting (IPTW) survival analysis to examine survival in pancreatic adenocarcinoma patients. Methods: In this population-based study, data from the Surveillance, Epidemiology, and End Results program of the United States were analyzed to identify patients diagnosed with adenocarcinoma of the pancreas 2004 to 2014. Differences in survival rates were examined among patients who underwent pancreatectomy alone, radiotherapy alone, and those who had pancreatectomy plus adjuvant radiotherapy. Kaplan–Meier estimates and Cox proportional hazards models with the IPTW were performed to determine the effect of different treatments on overall and cancer-specific survival. This study was approved by the Ethics Review Board of Weifang Medical University. Results: A total of 8191 patients were included, with 3409 taking pancreatectomy only, 2865 taking radiotherapy only, and 1917 taking pancreatectomy plus adjuvant radiotherapy. Patients who received surgery plus adjuvant radiotherapy had statistically a higher survival rate than those who received the other 2 treatments. Survival analysis with the IPTW for the 3 different groups showed that the difference in median overall survival time among these patient groups was significant. Conclusion: Using IPTW survival analysis, the present study shows that surgery with adjuvant radiotherapy is significantly associated with improved overall and cancer-specific survival among patients with pancreatic adenocarcinoma.